Local strain energy density to predict mixed mode I + II fracture in specimens made of functionally graded materials weakened by V-notches with end holes. (December 2017) - Mohammadi, H.; Salavati, H.; Mosaddeghi, M.R.; Yusefi, A.; Berto, F.
Highlights: Mixed mode fracture experiments on VO-notches made of W-Cu FGM are provided. An energy-based criterion is proposed to predict fracture of VO-notch made of FGM. The proposed criterion predicts well the experimental results. The effect of notch geometry on fracture load is theoretically elaborated. Abstract: The mixed mode fracture of specimens weakened by V-notches with end holes (VO-notch) made of W-Cu functionally graded material (W-Cu FGM) has been investigated in this paper. In experimental section, W-Cu FGM specimens were fabricated by powder metallurgy technique. A number of fracture tests were performed on VO-notched W-Cu FGM specimens under in-plane mixed mode for various notch tip radii, notch depths, and notch opening angles. In theoretical section, a criterion based on the averaged value of strain energy density over a well-defined control volume was proposed to predict the fracture loads of VO-notched FGM specimens under mixed mode I + II. In addition, the effect of notch geometrical parameters (notch tip radius, notch depth, and notch opening angle) on fracture load was studied. This study demonstrates that SED works well on VO-notched FGM specimens under mixed mode I + II loading.